Pemberdayaan Masyarakat Desa Semangat Karya Kabupeten Barito Kuala Melalui Kegiatan Akuaponik dan Budidaya Ikan dalam Ember (Budikdamber) - Fuzi Maulana Ash'ari; Gusti Khairun Ni'mah; Yarna Hasiani; Ilhamiyah Ilhamiyah (Abdimas Universal, 2023)
One of the ways to utilize the yard of the house is by using the aquaponics method and cultivating fish in buckets (budikdamber). The activity of keeping or raising fish using limited land is something that is quite difficult to do in the Semangat Karya Village, Barito Kuala Regency, which is dominated by swamps. There is no assistance in empowering village communities in fish farming activities, which is the main factor in the lack of community interest. Therefore, this service activity aims to provide knowledge and training to support skills in cultivating fish in buckets (budikdamber) and aquaponics. The method for implementing this service activity begins with filling out a pre-test questionnaire, presentation of material by the supervisor, then continues with a post-test and activities to assist participants in cultivating fish in buckets (budikdamber) and aquaponics. The result is an increase in knowledge, understanding and skills in bucket fish cultivation (budikdamber) and aquaponics in the village of Semangat Karya, Alalak District, Barito Kuala Regency.